Musical Tone Law Method for the Structural Damage Detection - Weisong Yang; Weixiao Xu; Xun Guo; Liguo Yang (Advances in Materials Science and Engineering)
Damage detection tests of inclined cables, steel pipes, spherical shells, and an actual cable-stayed bridge were conducted based on the proposed musical tone law method. The results show that the musical tone law method could be used in the damage detection of isotropic material structures with simple shape, like cables, pipes, plates, and shells. Having distinct spectral lines like a comb with a certain interval distribution rule is the main characteristic of the music tone law. Damage detection baseline could be established by quantizing the fitting relationship between modal orders and the corresponding frequency values. The main advantage of this method is that it could be used in the structural damage detection without vibration information of an intact structure as a reference.